Usim’s Legal Clinic And Divorce Casework: A Maqasid Al-shariah-based Socio-legal Study - Muhammad Nor Izzuddin NorizanNizan; Muhammad Anas Mohd Shaiful Nizam; Ahmad Iqbal Alfaruq Rosli; Ahmad Irfan Assiddiq Rosli; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
The rising divorce rate has become a significant social and legal concern in contemporary Malaysian society, particularly among Muslim couples. In Islam, divorce (talaq) is a lawful but regulated dissolution of the marital bond, which may also occur through fasakh by court order or khulu‘ at the wife’s request. Recent national statistics indicate a steady increase in divorce cases, commonly attributed to misunderstandings, financial hardship, and third-party interference. This study examines the role of USIM’s Legal Clinic as a community-based legal advisory service that assists couples in addressing domestic conflicts by Syariah principles and the objectives of Maqasid al-Shariah. Using a qualitative approach, this paper analyses how the Clinic’s services, including Alternative Dispute Resolution (ADR) mechanisms such as mediation and sulh, facilitate the amicable resolution of disputes, alleviate the burden on the Syariah Court, and offer cost-effective solutions. Expanding E-Consultation services further enhances public access to personalised legal guidance and timely support. Additionally, this research explores the broader legal challenges couples face within the Syariah system, including claims for maintenance, child custody, and the division of matrimonial assets. By delivering accessible legal advice and dispute resolution support, the USIM Legal Clinic serves as an effective early intervention model that upholds core Maqasid al-Shariah objectives: preserving family harmony, protecting individual dignity (hifz al-‘ird), and promoting justice and social welfare. The findings highlight the importance of strengthening such community-oriented institutions to address divorce-related issues comprehensively and to ensure that practical legal assistance aligns with the higher aims of Islamic law in contemporary Malaysia.